A qualitative study of childbirth fear and preparation among primigravid women: The blind spot of antenatal care in Lilongwe, Malawi - Berlington M.J. Munkhondya; Tiwonge Ethel Munkhondya; Gladys Msiska; Ezereth Kabuluzi; Juqin Yao; Honghong Wang (Elsevier, 2020)
Objectives: This study aimed to explore childbirth fear and childbirth preparation among primigravid women in the late pregnancy from 36 to 40 weeks gestation. Methods: We purposively recruited 18 primigravid women into in-depth interviews, 21 birth companions, and 13 health workers into focus group discussions. Participants were recruited from two community hospitals' maternity waiting homes in Lilongwe, Malawi. Semi-structured interview guides were used to collect data that were analyzed using content analysis. NVivo11 computer software was used to organize the data. Results: The four categories developed were: "ambivalent pregnancy feelings" , "dependence on traditional childbirth counseling" ,"inadequate prenatal childbirth instruction" and "inconsistent roles of a birth companion" . The findings suggest that primigravid women who were mainly exposed to traditional childbirth mentoring rather than professional care providers, experienced childbirth fear, and lacked proper psychosocial childbirth preparation. Conclusions: Childbirth fear among primigravid women emanate from personal; family; ineffective traditional counseling; and inadequate antenatal childbirth instruction. Birth companions may increase childbirth stress. However, our findings highlight birth companions as readily available psychosocial support resources among primigravid women. We recommend that professional childbirth instruction during antenatal care should be strengthened to surpass traditional childbirth counseling. Appropriateness and effectiveness of birth companions need to be carefully assessed.